2013
DOI: 10.1111/jpn.12132
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of type I collagen cDNA and nutritional regulation of type I collagen mRNA expression in grass carp

Abstract: Grass carp (Ctenopharyngodon idellus) are important Chinese freshwater fish, and in China, the faba bean has been used as the sole food source for grass carp to transform them into crisp grass carp. Because of this, crisp grass carp has become an economically important fish because of its increased muscle hardness. To study the nutritional regulation of type I collagen in faba bean-fed grass carp, we isolated type I collagen alpha 2 (COL1A2) on the basis of our isolation of COL1A1. The COL1A2 cDNA was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…The “crisp” quality of the flesh of crisp grass carp after cooking is a typical characteristic of this fish variety3. The significantly increased chewiness of crisp grass carp muscle compared with that of ordinary grass carp is an important contributor to this “crispness”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “crisp” quality of the flesh of crisp grass carp after cooking is a typical characteristic of this fish variety3. The significantly increased chewiness of crisp grass carp muscle compared with that of ordinary grass carp is an important contributor to this “crispness”.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1970s, fish farmers in Dongsheng Town, Guangdong Province, China, accidentally discovered that the muscle structure of grass carp changed significantly after they were fed with faba bean ( Vicia faba L.) solely for 90–120 days. Unlike ordinary grass carp, this carp variety when fed with faba bean exhibited a significant increase in muscle hardness and crispiness, and thus became popular among local people3.…”
mentioning
confidence: 99%
“…The main collagen in fish muscle and skin is type I collagen (Eckhoff, Aidos, Hemre, & Lie, ; Sato et al, ; Yata et al, ), which is encoded by two α1 chains (COL1A1) and one α2 chain (COL1A2). The COL1A1 and COLlA2 proteins of grass carp were found to be highly hydrophilic (Liu et al, ; Yu et al, ). A higher hydrophilic capability can promote the ability to combine with other substances and can thus enhance the function and the elasticity of tissues as well as the water‐holding capacity, which is consistent with Lapière's () findings of type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…A higher hydrophilic capability can promote the ability to combine with other substances and can thus enhance the function and the elasticity of tissues as well as the water‐holding capacity, which is consistent with Lapière's () findings of type I collagen. Studies have shown that the relative expression of type I collagen mRNA and the protein expression of COL1A1 and COL1A2 genes of crisped grass carp were significantly higher than those of common grass carp (Yu et al, ). The present study also indicated the increased expression of COL1A1 and COL1A2 mRNA in muscle and skin by feeding broad bean‐based diets and SBB but not in the liver, which was consistent with the collagen content pattern in tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation